Psychological mechanisms of the emergence of interests between asymmetric partners in business-ecosystems - Maslianchuk, Viktoriia (Здобутки економіки: перспективи та інновації, 2025)
In the modern business environment, where asymmetric partnerships are becoming increasingly widespread, the study of the psychological mechanisms for harmonizing interests between parties is particularly relevant. The purpose of this study is to identify factors that facilitate or, conversely, complicate effective interaction among partners across different resource conditions and cultural contexts, and to formulate proposals for building practical, long-term cooperation. The study used theoretical methods such as analysis, synthesis, abstraction, induction, and deduction to evaluate theories of the psychological mechanisms underlying conflict and cooperative behavior. Empirical methods, particularly descriptive methods, were used to collect data on the influence of cultural and social context on trust and communication between partners. Theories of harmonization of interests based on rational choice and socio-psychological principles were analyzed. It is shown that integrating individual, interpersonal, and organizational mechanisms creates a synergistic effect that mitigates asymmetry and promotes long-term cooperation between partners. The need for a comprehensive approach to harmonizing interests in partnership relations is noted, in which collective values serve as a key mechanism for control and mutual understanding, fostering a trustful atmosphere. It is noted that managed conflict can act as a catalyst for building trust and opening up opportunities for open dialogue, provided that the parties' cultural characteristics are taken into account. Based on the data obtained, practical recommendations for the corporate sector have been developed, including the introduction of educational programs and coaching to develop emotional competence, formalized reporting procedures and transparent communication channels. The importance of digital platforms for regular interaction and active listening practices as a means of harmonizing interests in partnership relations in conditions of role asymmetry is noted. It has been proven that shared values and strategic goals are the basis for building trust and mutually beneficial partnerships, and that psychological mechanisms are an effective tool for mitigating the negative consequences of asymmetry and creating conditions for identifying and implementing mutually beneficial points of intersection of interests.